B-lymphocyte subpopulations in patients with selective IgA deficiency - Nechvatalova, Jana; Pikulova, Zdenka; Stikarovska, Dagmar; Pesak, Sava; Vlkova, Marcela; Litzman, Jiri (Journal of clinical immunology, 2012)
INTRODUCTION: Selective deficiency IgA (IgAD) is the most common primary abnormality of immunoglobulin production with unknown pathophysiology. It is genetically related to common variable immunodeficiency (CVID), where besides IgA also IgG and frequently IgM serum levels are decreased. In this study we focused on determination of B-lymphocyte developmental stages and searching for similarities between CVID and IgAD. MATERIALS AND METHODS: Using flow cytometry we determined major lymphocyte subpopulations and B-lymphocyte subsets: naïve (CD27(-)IgD(+)), marginal zone cells (CD27(+)IgD(+)), class-switched memory cells (CD27(+)IgD(-)), "double-negative" B cells (CD27(-)IgD(-)), transitional cells (IgM(++)CD38(++)), plasmablasts (CD38(+++)IgM(+) or IgM(-)), and CD21(low)CD38(low) cells in 80 patients with IgAD, 48 patients with CVID, and 80 control persons. RESULTS: Compared to healthy controls, a decrease in the absolute number and frequency of CD4+ cells (both < 0.001) was observed in IgAD patients. A decrease in the frequency of switched memory cells (P < 0.001), transitional cells (P = 0.035) as well as plasmablasts (P < 0.001) and an increase in the CD21(low)CD38(low) subset (P = 0.007) was observed in IgAD patients compared to control persons. No significant differences were observed in the remaining B-cell developmental subsets. A decrease in CD27(+)IgD(-) (<0.4% of peripheral blood lymphocytes), frequently observed in CVID patients and also previously reported in IgAD, was found in only five patients (6%) with IgAD, two of them being first-degree relatives of CVID patients. CONCLUSION: Our results show a decrease of terminally differentiated B-lymphocyte subsets in patients with IgAD, similar as previously found in patients with CVID, but these results are less expressed than in CVID patients.
Keywords: buněčná diferenciace; Humans; lidé středního věku; IgA Deficiency; podskupiny B-lymfocytů; běžná variabilní imunodeficience; Female; Aged; mladý dospělý; dospělí; senioři; lidé; B-Lymphocyte Subsets; Adult; ženské pohlaví; Male; Middle Aged; Adolescent; Cell Differentiation; Aged, 80 and over; Young Adult; senioři nad 80 let; mužské pohlaví; Common Variable Immunodeficiency; mladiství; deficience IgA